Effectiveness assessment of riluzole in the prevention of oxaliplatin-induced peripheral neuropathy: RILUZOX-01: protocol of a randomised, parallel, controlled, double-blind and multicentre study by the UNICANCER-AFSOS Supportive Care intergroup. Issue 6 (9th June 2019) - Kerckhove, Nicolas; Busserolles, Jérome; Stanbury, Trevor; Pereira, Bruno; Plence, Valérie; Bonnetain, Franck; Krakowski, Ivan; Eschalier, Alain; Pezet, Denis; Balayssac, David
Abstract : Introduction: Most patients (>70%) experience acute neuropathic symptoms shortly after oxaliplatin infusions. These symptoms are not always resolved between infusions. Overall, 30%–50% of patients suffer from chronic oxaliplatin-induced peripheral neuropathy (OIPN). This cumulative and dose-dependent sensory neuropathy limits compliance or results in oxaliplatin-based chemotherapies to be substituted with less neurotoxic agents. These treatment changes impair clinical outcomes, and may be associated with comorbidities, such as distress, depression and anxiety. Currently, no drug used to prevent or treat OIPN is sufficiently effective to be used routinely in clinical practice. There is, thus, an unmet therapeutic need to reduce the intensity of and/or prevent OIPN. We hypothesised that riluzole would be an excellent candidate to address this public health issue. Riluzole is approved for treating amyotrophic lateral sclerosis. In animals, there is a beneficial effect on sensorimotor and pain disorders, as well as related comorbidities, after repeated administration of oxaliplatin. In humans, riluzole has shown neuroprotective, anxiolytic and antidepressive effects. Methods and analysis: RILUZOX-01 trial was designed as a randomised, controlled, double-blind study to evaluate the efficacy of riluzole to prevent OIPN. Patients with colorectal cancer and initiating adjuvant oxaliplatin-based chemotherapy are eligible. Patients (n=210) will be randomly assigned to either riluzole or placebo, concomitantly with chemotherapy. The primary endpoint is the change in OIPN intensity, assessed by the sensory scale of the QLQ-CIPN20, after six 2-week cycles of chemotherapy. Secondary endpoints include incidence and severity of neuropathy, grade of sensory neuropathy, intensity and features of neuropathic pain, health-related quality of life, disease-free survival, overall survival and safety. Ethics and dessimination: The study was approved by a French ethics committee (ref:39/18_1, 'Comité de Protection des Personnes' Ouest-IV, France) and plans to start enroling patients in September 2019. The trial is registered in EudraCT and clinicaltrials.gov. Trial registration number: N°2017-002320-25; NCT03722680